Antidepressant bupropion exerts alleviating properties in an ovariectomized osteoporotic rat model - Abuohashish Hatem M; Ahmed Mohammed M; Al-Rejaie Salim S; ELTahir Kamal EH (Acta Pharmacologica Sinica, 2017)
Aim: Depression is a risk factor for impaired bone mass and micro-architecture, but several antidepressants were found to increase the incidence of osteoporotic fractures. In the present study we used ovariectomized (OVX) rats as a model of osteoporosis to investigate the effects of the antidepressant bupropion on the femoral bones. Methods: OVX animals were treated with bupropion (30, 60 mg·kg-1·d-1) for six weeks. Bone turnover biomarkers (urinary DPD/Cr ratio, serum BALP, OC, TRAcP 5b, CTX and sRANKL levels) and inflammatory cytokines (TNF-α, IL-1β and IL-6) were determined using ELISA. Inductively coupled plasma mass spectroscopy (ICP-MS) was used to determine the femoral bone mineral concentrations. The cortical and trabecular morphometric parameters of femoral bones were determined using micro-CT scan and histopathology. Results: In OVX rats, the levels of bone turnover biomarkers and inflammatory cytokines were significantly elevated and femoral bone Ca2+ and PO4 3- concentrations were significantly reduced. Moreover, cortical and trabecular morphometric parameters and histopathology of femoral bones were severely altered by ovariectomy. Bupropion dose-dependently inhibited the increases in bone turnover biomarkers and inflammatory cytokines. OVX rats treated with the high dose of bupropion showed normal mineral concentrations in femoral bones. The altered morphometric parameters and histopathology of femoral bones were markedly attenuated by the treatment. Conclusion: Bupropion exerts osteo-protective action in OVX rats through suppressing osteoclastogenesis-inducing factors and inflammation, which stabilize the osteoclasts and decrease bone matrix degradation or resorption.